2018
DOI: 10.1186/s41610-018-0082-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of LEDs and duty ratio on the growth and physiological responses of Silene capitata Kom., endangered plant, in a plant factory

Abstract: Background: In this study, we observed their growth and physiological responses using a variety of duty ratio under the mixed light using red, blue, and white lights. The red+blue mixed light was treated with 95%, 90%, 85%, 80%, and 75% duty ratios and red+blue+white mixed light with 85% and 70% duty ratios. We examined the width and length of leaves, total number of leaves, and number of shoots to examine their growth responses. The physiological responses were studied by measuring their photosynthetic rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Besides light stress, a decreasing trend in Fv/Fm by reducing Fm was also observed under stress from heat, ozone, and other pollutants [49,51]. Interestingly, Fv/Fm was found higher in the white, R:B:W, and R:B:G ratio in some previous studies [41,52], which quite supports our present findings. PCA analysis revealed that Chl a, Chl b, and Fv/Fm were negatively correlated with Pro, AsA, RL, PFW, and Car (Figure 7).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Besides light stress, a decreasing trend in Fv/Fm by reducing Fm was also observed under stress from heat, ozone, and other pollutants [49,51]. Interestingly, Fv/Fm was found higher in the white, R:B:W, and R:B:G ratio in some previous studies [41,52], which quite supports our present findings. PCA analysis revealed that Chl a, Chl b, and Fv/Fm were negatively correlated with Pro, AsA, RL, PFW, and Car (Figure 7).…”
Section: Discussionsupporting
confidence: 92%
“…Similar results from a previous study described that a high ratio of both R:B and R:B:W manifested higher chlorophyll compared to natural light in Silene capitate Kom. [41]. Each of the plant pigments has been characterized by an absorbance pattern in wavelength called the absorbance spectrum, where the blue and red regions are absorbed strongly by Chl a and b, with less absorbance of other wavelengths [42].…”
Section: Discussionmentioning
confidence: 99%